2019
DOI: 10.1093/noajnl/vdz034
|View full text |Cite
|
Sign up to set email alerts
|

Management of cutaneous neurofibroma: current therapy and future directions

Abstract: Neurofibromatosis type 1 (NF1) is a life-long neurocutaneous disorder characterized by a predisposition to tumor development, including cutaneous neurofibroma (cNF), the hallmark of the disease. cNF is a histologically benign, multicellular tumor formed in virtually most individuals with NF1. It is considered the most burdensome feature of the disorder due to their physical discomfort, cosmetically disfiguring appearance, and psychosocial burden. Management of cNF remains a challenge in the medical field. Effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 78 publications
0
37
0
Order By: Relevance
“…Surgical removal, laser ablation, modified biopsy removal, photocoagulation, electrodessication and radiofrequency ablation are the modalities that have been developed. Camouflage and moisturizers may also provide some relief for patients [ 34 ]. In a previous study, topical imiquimod has shown some volume reduction.…”
Section: Neurofibromasmentioning
confidence: 99%
“…Surgical removal, laser ablation, modified biopsy removal, photocoagulation, electrodessication and radiofrequency ablation are the modalities that have been developed. Camouflage and moisturizers may also provide some relief for patients [ 34 ]. In a previous study, topical imiquimod has shown some volume reduction.…”
Section: Neurofibromasmentioning
confidence: 99%
“…If admixed with nerves, preservation of nerve is of utmost importance. [ 9 10 ] Recently, FDA has approved Selumetinib (MEK inhibitor) for symptomatic neurofibromas.…”
Section: Discussionmentioning
confidence: 99%
“…First presenting with hyperpigmentation-like cafe-au-lait macules and freckling in afflicted patients, the hallmark of NF1 is the development of neurofibromas, benign tumors composed of an admixture of dysplastic Schwann cells and stromal cells, including fibroblasts, mast cells, and perineural cells embedded in a collagenous extracellular matrix (ECM). Nearly all NF1 patients develop cutaneous neurofibromas (CNFs, or dermal neurofibroma), which arise along superficial nerves and are confined to the cutaneous tissues (6). CNFs can cause itching and pain.…”
Section: Neurofibromatosis (Nf) Comprises Three Distinct Genetic Disorders That Cause Tumors To Grow Along Nervesmentioning
confidence: 99%
“…For current NF1 treatment, surgical excision of CNFs can be performed when symptomatic (6). Surgical removal of PNFs is more challenging because they are more diffuse and involve multiple nerve roots.…”
Section: Neurofibromatosis (Nf) Comprises Three Distinct Genetic Disorders That Cause Tumors To Grow Along Nervesmentioning
confidence: 99%
See 1 more Smart Citation